Analysis of Web-Based E-Commerce Testing Using Black Box and White Box Methods - Mhd Dion Gustinov; Nilam Wahdiaz Azani; Rahmat Al Ghani; Sephia Nazwa Auliani; Sisri Maharani; Muhammad Luthfi Hamzah; Muhammad Rizki (International Journal of Information System and Innovation Management (IJISIM), 2023)
The Shoopers application is an E-Commerce application that offers its services through the website. During its journey, this application must be able to serve and provide convenience to its users. The launch of this website was carried out in 2021, but there are still reports from users complaining that some features are not working. used. The purpose of this study is to test all website functions. After the black-and-white-box testing methodology, the results show that there are still inputs whose results are not as expected and will later have an impact on the customer database. By carrying out this test the researcher was able to test the Shopers application and find out the shortcomings of the program so that it could be developed further.